Perceptions and Suggestions Towards Adolescent Sexuality Education Among Secondary School Teachers in Region 1, The Gambia - Ina Grant Sagnia, Phebian; Dally Bittaye, Fatou; Hamadi Secka, Michael (Journal of Public Health International, 2025)
Comprehensive Sexuality Education (CSE) is a school-based intervention aimed at correcting misinformation surrounding sexual education among youth, often influenced by social media, peer groups and misleading online content. In The Gambia, the Ministry of Basic and Secondary Education has developed and introduced a national framework to integrate CSE from Grade 4 (primary school level) to Grade 12 (senior secondary school level). This study explores the perceptions and recommendations of 50 secondary school teachers from 43 public and private schools in Region 1 on the implementation of CSE in schools. While some teachers expressed concerns that CSE might promote perverted and lewd early sexual behavior, others saw it as essential for increased awareness and youth well-being. Cultural, religious, and societal norms pose significant implementation barriers towards the implementation of CSE in schools. Teachers’ insights are vital for successful CSE delivery and educational strategy improvements.
Keywords: Comprehensive Sexuality Education; Teachers; Adolescents; Secondary School; The Gambia